Validation of the procedure: Quantification of the degradation index of Photovoltaic Grid Connection Systems - Proenza Y. Roger; Camejo C. José Emilio; Ramos H. Rubén (Journal La Multiapp, 2021)
The results obtained from the validation of the procedure ‟Quantification of the degradation index of Photovoltaic Grid Connection Systems” are presented, using statistical parameters, which corroborate its accuracy, achieving a coefficient of determination of 0.9896, a percentage of the root of the mean square of the error RMSPE = 1.498% and a percentage of the mean absolute error MAPE = 1.15%, evidencing the precision of the procedure.